Implementing enhanced recovery pathways to improve surgical outcomes - Shilpadevi Patil; Elyse M Cornett; June Jesunathadas; Kumar Belani; Charles J Fox; Alan David Kaye; Lee A Lambert; Richard D Urman (Wolters Kluwer Medknow Publications, 2019)
An enhanced recovery pathway is a structured perioperative healthcare program that incorporates evidence-based interventions including protocols and guidelines with the aim of providing standardized care. Enhanced recovery pathways can help maintain operating room safety and efficiency, improve postoperative recovery and a variety of important patient outcomes, and reduce overall costs of patient care following major surgery. Postoperative complications are minimized, which, in part, are attributed to adjustments in fasting and postoperative nutrition, interventions aimed at improving early mobilization, and careful selection of pharmacological agents for anesthesia and analgesia. Major surgery can lead to a variety of physiological stressors including organ dysfunction, and hormonal and neurological disturbances. The current notion of fast-tracking (bypassing phase I recovery level of care) differs from enhanced recovery pathways as the principles of enhanced recovery pathways are often applied to inpatient and complex procedures and span the entire spectrum of patient care. Also, enhanced recovery pathways programs are being used for pediatric patients especially with the hope of minimizing opioid exposure and the quality of recovery. A PubMed literature search was performed for articles that included the terms enhanced recovery pathways to improve surgical outcomes. In this article, we summarized the clinical application of enhanced recovery pathways and highlighted the key elements that characterize implementing an enhanced recovery pathway in surgery.